Defending a Contested Ideal: Merit and the Public Service Commission, 1908–2008 - Juillet, Luc; Rasmussen, Ken (Les Presses de l'Université d'Ottawa / University of Ottawa Press, 2008)
In 1908, in order to combat the patronage that undermined both the effectiveness of public administration and democratic practices, the Canadian Parliament decided that public servants would be selected on the basis of merit, through a system to be administered by an independent agency: the Public Service Commission of Canada. Published on the occasion of the commission's centenary, this book recounts its history and that of the merit principle, which was born of controversy and has since been the subject of countless debates. It also explains the commission's outstanding resilience and shows its unique contribution to the development of an independent public service, which has been an important pillar of Canadian parliamentary democracy. The book also describes how the commission has contributed through the years to finding an evolving balance among three related, but sometimes conflicting, objectives associated with staff the public service of a liberal democracy: political neutrality, democratic equality and managerial efficiency.
1. The Origins of the Public Service Commission: 1867-1918 2. Creating a Merit System: 1918-1944 3. Rethinking the CSC: Gordon, Heeney and Glassco: 1945-1967 4. The Management Assault on the Public Service Commission: 1967-1979 5. Struggling to Defend Political Neutrality: 1979-2006 6. The PSC as a Cautious Reformer: Staffing Reforms during the Mulroney Years: 1984-1993 7. Merit as the Essential Mandate: Repositioning the PSC: 1993-2008